2012
DOI: 10.1007/s00455-012-9425-x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age, Sex, Bulb Position, Visual Feedback, and the Order of Testing on Maximum Anterior and Posterior Tongue Strength and Endurance in Healthy Belgian Adults

Abstract: This study collected data on the maximum anterior and posterior tongue strength and endurance in 420 healthy Belgians across the adult life span to explore the influence of age, sex, bulb position, visual feedback, and order of testing. Measures were obtained using the Iowa Oral Performance Instrument (IOPI). Older participants (more than 70 years old) demonstrated significantly lower strength than younger persons at the anterior and the posterior tongue. Endurance remains stable throughout the major part of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
116
4
24

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(167 citation statements)
references
References 26 publications
23
116
4
24
Order By: Relevance
“…In the recent studies, tongue pressure and masticatory performance were positively correlated in a sample of young adults (Takahashi et al, 2013); additionally, significant differences in maximum tongue pressure were found between males and females in young adults (Takahashi et al, 2013; Vanderwegen, Guns, Van Nuffelen, Elen, & De Bodt, 2013). The findings were consistent with their results.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the recent studies, tongue pressure and masticatory performance were positively correlated in a sample of young adults (Takahashi et al, 2013); additionally, significant differences in maximum tongue pressure were found between males and females in young adults (Takahashi et al, 2013; Vanderwegen, Guns, Van Nuffelen, Elen, & De Bodt, 2013). The findings were consistent with their results.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies showed that maximum tongue pressure remained constant from 20s to 60s and started to decrease from the 70s in females (Utanohara et al, 2008; Vanderwegen et al, 2013). We suggest that females need training with respect to tongue pressure, by the mixed dentition stage, to increase the peak of tongue pressure.…”
Section: Discussionmentioning
confidence: 99%
“…This fact can be justified, because, in these tasks, the participants had to press the bulb as much as possible; from the three measurements taken, the highest value was considered (13,14,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) . Therefore, even though the values in the elevation task did not differ between the genders, the factor more muscle mass in the tongue, besides height and weight (11,12) , among male participants may have contributed for the similar values found in these tasks.…”
Section: Discussionmentioning
confidence: 99%
“…It was selected this age interval to exclude the effect of reduced muscle strength due to aging [8][9][10] . The inclusion criteria were: (a) being a native Portuguese speaker, (b) to be within the age group and (b) to give written consent authorizing participation in the research.…”
Section: Participantsmentioning
confidence: 99%